Penerapan Islamic Moral Values dalam Pembentukan Karakter Mahaisswa melalui Budaya Organisasi - Zaini, Moh.; Ulum, Bachrul; Kusmawati, Wiwik; Siska Sari, Reno (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
This research aims to provide an overview of the integration of Islamic moral values that can influence the formation of student character in organizations. Additionally, it seeks to present the essential values for building student character in an organizational environment and to offer an Islamic moral development approach that can be effectively applied within the culture of student organizations. This study employs a qualitative approach, specifically library research. In the analysis process, the researchers used Miles & Huberman's content analysis. The stages carried out include data accumulation, which involves reading, recording, and managing the necessary research materials, followed by displaying the data, data condensation, data reduction, data verification, and conclusion. This process aims to provide insights related to the phenomenon while offering solutions to the core problem that is the focus of the research. Upon completing the data analysis process, the researchers formulate conclusions in the form of descriptive findings. The results of this research indicate that the integration of Islamic moral values plays a significant role in shaping student character within organizational environments, particularly in fostering honesty, responsibility, and social awareness. The values that can serve as a foundation for this formation include trust, mutual assistance, and respectful communication. These values underscore the importance of maintaining ethical standards in interactions and collaboration within the organization. This can be instilled through knowledge, habituation, and exemplary conduct (uswah hasanah).